SISTEM PENDUKUNG KEPUTUSAN DALAM PENENTUAN PENERIMA RASTRA (BERAS SEJAHTERA) MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (STUDI KASUS DESA KARANG BANGUN) - Sinaga, Dicky Hartama; Tambunan, Heru Satria; Jalaluddin, Jalaluddin (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Decision Support System (SPK) is a computer-based system that combines models and data in an effort to solve unstructured problems with user involvement through an easy-to-use user interface. This system is used to help decision making in semitructured situations and unstructured situations, where no one knows for sure how decisions should be made. Simple Additive Weighting method is one of the settlement methods for Multi attribute decision making (MADM) problems. This method evaluates several alternatives to a set of attributes or criteria, where each attribute does not depend on each other. Hope from the results of the study, the use of Simple Additive Weighting as a model of the Eligible Decision Support System for Rastra Assistance using the weighted product method in Karang Bangun Village, Siantar Subdistrict, Simalungun Regency can help the village in calculating the feasibility of rice recipients and to determine the eligibility of recipients of rice faster and more accurate. because this application is easier than the old system and the data storage is more accurate.Keywords: Decision Support Systems, Simple Additive Weighting, Rastra, Poor